ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI BAWANG MERAH LOKAL PALU DI DESA SOULOVE KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Hijrayanti, Hijrayanti; Laapo, Alimuddin; Tangkesalu, Dance (AGROTEKBIS, 2018)
Onion local Palu (Allium cepa L. group Agregatum) is industrial raw material of processing friend onion which has been become the best product in Palu. This research aims to find out the effect of production inputs of land area, seed, fertilizer and labor usage on onion production at soulove village of Sigi Biromaru subdistrict of Sigi regency. Furthermore, this research aims to find out the level of efficiency of production inputs of the farm usage. Determination of sample used is simple random sampling method. The data analysis used is correlation analysis, Cobb-Douglass, production, and efficiency. The research results showed that simultaneously, all independent variables (X) give real effect on the dependent variable (Y). The analysis results showed that silmultaneously, factors of land area (X1), labor (X2), seed (X3), and fertilizer (X4) give very significant effect on the production of onion farming, with Fcount> Ftable on α 1 % level. The results of t-test showed that land area, fertilizer, and labor have no significant effect with tcount<ttable. On α 1% level, whereas the seed have a real effect with tcount> ttable.Results of efficiency analysis show the k value from seed variable, numbers > 1 means production inputs used in onion farming at soulove village of Sigi Biromaru subdistrict of  Sigi regency in terms of price utilization input production were declared not efficient yet, while the use of land area input, fertilizer and labor in terms of inefficient prices.